Memoria MAC 1998-2005. (Santiago de Chile : MAC - Museo de Arte Contemporaneo Santiago de Chile, 2006)
Abarca, Agustin ; Antunez, Nemesio ; Van Asperen, Mónica ; Babarovic, Natalia ; Balmes, José ; Bate, Monica ; Biao Zhong ; Bogni, Carlos ; Bonta, Marco ; Bru, Roser ; Bruna, Rodrigo ; Carbo, Enriqué ; Carreño, Alexis ; Carrera, Angel ; Carril, Delia del ; Castañeda, Paz ; Céspedes, Juan ; Correa, Magdalena ; Corvalan, Maximo ; Cristi, Ximena ; Cucchi, Enzo ; Davila, Juan ; Diaz, Gonzalo ; Donoso, Catalina ; Durán, Andrés ; Egenau, Juan ; Equipo Cronica ; Equipo Limite ; Errázuriz, Paz ; Espa, Virginia ; Evaristti, Marco ; Fontecilla, Josefina ; Förterer, Holger ; Godoy, Javier ; Guilisasti, Josefina ; Gumucio, Ignacio ; Hausmann, Raoul ; Hermosilla, Carlos ; Hidalgo, Juan ; Hu Youben ; Ianiszewski, Jorge ; Isamitt, Carlos ; Jardine, Bob ; Kobayashi, Yashihito ; Lamouroux, Vincent ; Ledezma, Loreto ; Lehyt, Cristobal ; Lorenzini, Kena ; Maggi, Marco ; Marco, Angeles ; Mariscal, Javier ; Martinez Bonatti, Eduardo ; Martinez, Victoria ; Maruscenko, Viktor ; Matta (Roberto Antonio Sebastian Matta Echaurren) ; Matthews, Mariana ; Maury, Carolina ; Mezza, Gonzalo ; Montes, Maria Francisca ; Moraga, Marcela ; Nauman, Bruce ; Niemetz, Anne ; Ohki, Masato ; Ono, Yoko ; Opazo, Jorge ; Oyarzun, Bernardo ; Oyola, Alexis ; Palma, Cristobal ; Paz Zamorano, Maria ; Perez, Claudio ; Perez, Matilde ; Perotti, José ; Poblete, Gustavo ; Preece, Sebastian ; Yufen Qin ; Rivera, Daniela ; Rivera, Pablo ; Rojas, Luis ; Rojas, Sergio ; Roman, Samuel ; Rosenfeld, Lotty ; Samakh, Erik ; Shaofeng Chen ; Soobhany, Manou ; Steeger K., Patrick ; Tunick, Spencer ; Ueno, Guillermo ; Ugalde, Gastón ; Valenzuela, Tomas ; Vergara Grez, Ramon ; Vial, Ivan ; Villablanca, Joe ; Vostell, Wolf ; Wennberg, Teresa ; Z, Claudio ; Z, Mario
lijst met tent. en activiteiten p. 159-188
Spaans
boek